Sexual satisfaction among lesbian and heterosexual cisgender women: a systematic review and meta-analysis - Macedo, Ana (2023)
Background: Sexual satisfaction is a complex, multifaceted, and broad concept that is influenced by several factors. The minority stress theory posits that sexual and gender minorities are at a particular risk for stress due to stigma and discrimination at the structural, interpersonal, and individual levels. The aim of this systematic review and meta-analysis was to evaluate and compare the sexual satisfaction between lesbian (LW) and heterosexual (HSW) cisgender women. Methods: A systematic review and meta-analysis were conducted. We searched the PubMed, Scopus, Science Direct, Websci, Proquest, and Wiley online databases from 1 January 2013 to 10 March 2023 to identify the published observational studies on sexual satisfaction in women according to their sexual orientation. The risk of bias in the selected studies was assessed using the JBI critical appraisal checklist for the analytical cross-sectional studies. Results: A total of 11 studies and 44,939 women were included. LW reported having orgasms during a sexual relationship more frequently than HSW, OR = 1.98 (95% CI 1.73, 2.27). In the same direction, the frequency of women reporting “no or rarely” for having orgasms during their sexual relationships was significantly lower in the LW than the HSW, OR = 0.55 (95% CI 0.45, 0.66). The percentage of the LW who reported having sexual intercourse at least once a week was significantly lower than that of the HSW, OR = 0.57 for LW (95% CI 0.49, 0.67). Conclusions: Our review showed that cisgender lesbian women reached orgasm during sexual relations more often than cisgender heterosexual women. These findings have implications for gender and sexual minority health and healthcare optimization.